2012
DOI: 10.1016/j.fertnstert.2011.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function during controlled ovarian hyperstimulation as part of in vitro fertilization

Abstract: Objective To determine the exact nature and timing of alterations in thyroid function throughout controlled ovarian hyperstimulation (COH). Design Prospective cohort study. Setting University fertility clinic. Patient(s) Fifty-seven women undergoing COH as part of planned in vitro fertilization. Intervention(s) None. Main Outcome Measure(s) Timing and magnitude of change in serum thyroid hormones, including TSH, total and free T4, E2, and thyroxine-binding globulin (TBG), measured at six time points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 25 publications
4
45
1
8
Order By: Relevance
“…In our "positive" subjects, the mean HCG level in "pregnant" group was 364 IU/L compared to negative (being<10 mIU/L). These findings are in keeping with those of Gracia et al [14] who also found higher TSH levels after COH.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our "positive" subjects, the mean HCG level in "pregnant" group was 364 IU/L compared to negative (being<10 mIU/L). These findings are in keeping with those of Gracia et al [14] who also found higher TSH levels after COH.…”
Section: Discussionsupporting
confidence: 93%
“…A systematic review of thyroid function during ART was inconclusive and highlighted the need for further studies [20]. Another recent study involving 57 patients showed TSH levels rise after IVF reaching a peak 1 week after HCG trigger [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we do not routinely check thyroid antibody status or free thyroxine on patients with TSH levels < 5.0 mIU/L; therefore, these values were not consistently available for analysis. Pre-treatment TSH levels may not fully represent thyroid function during fertility treatment, as there are data suggesting that TSH levels fluctuate during stimulated cycles [5]. Since this study focused on women undergoing assisted reproductive technology at a single institution, the results may not be generalizable to women undergoing natural conception attempts or those who conceive spontaneously.…”
Section: Discussionmentioning
confidence: 93%
“…Given its relevance to reproduction and pregnancy, women with infertility are routinely screened for thyroid function with serum thyroid-stimulating hormone (TSH) prior to elective fertility treatment [4]. Since there is evidence that ovarian stimulation may impact thyroid function [5], timely recognition of thyroid disease prior to initiating fertility treatment may be essential to optimizing outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Whether alterations of thyroid function during OH could influence ART and pregnancy outcomes is unclear. Several studies have evaluated thyroid parameters during OH, [11][12][13][14] or in the first month of pregnancy after OH. [15][16][17] However, the evidence concerning the effect of OH on thyroid function is contradictory, 18 probably due to the fact that alterations in thyroid function during OH are dependent on the duration and the amount of increment in E 2 levels.…”
Section: Introductionmentioning
confidence: 99%